CD2AP mutations are associated with sporadic nephrotic syndrome and focal segmental glomerulosclerosis (FSGS) - Gigante, Maddalena; Pontrelli, Paola; Montemurno, Eustacchio; Roca, Leonarda; Aucella, Filippo; Penza, Rosa; Caridi, Gianluca; Ranieri, Elena; Ghiggeri, Gian Marco; Gesualdo, Loreto (Nephrology, dialysis, transplantation, 2009)
Background. CD2-associated protein (CD2AP) is a crucial protein for the slit-diaphragm assembly and function. In spite of the fact that CD2AP knockout causes nephrotic syndrome in mice and the heterozygous +/− mouse is prone to proteinuria, little is known about the relevance of this molecule in human renal pathology. Methods. A total of 80 Italian patients with idiopathic nephrotic syndrome were enrolled and screened for changes in the CD2AP gene. A normal control group of 200 healthy donors was also studied. The coding region of the CD2AP gene was analysed by polymerase chain reaction, denaturing high-performance liquid chromatography and sequencing. Peripheral blood mononuclear cells from patients with CD2AP mutations and from healthy donors were isolated by the Ficoll–Hypaque gradient, and the CD2/CD2AP interaction was studied on T-lymphocytes by confocal laser scanning microscopy analysis. The expression levels of CD2AP, nephrin and podocin proteins were evaluated by indirect immunofluorescence on renal biopsies from a patient with p.delGlu525 mutation and from control subjects. Moreover, the effect of the p.K301M mutation on cell viability was evaluated by flow cytometry and annexin V/propidium iodide staining. Results. Three heterozygous mutations (c.904A>T; c.1120A>G; c.1573delAGA) producing respectively aminoacidic changes (p.K301M, p.T374A) or a deletion in functional domains (p.delGlu525) were found in three unrelated patients. One (p.K301M) produced a lysine to methionine change in the third interactive SH3 domain (position 301) and resulted in the defective CD2–CD2AP interaction and clustering; the other (c.1573delAGA) caused the deletion of the glutamic acid in position 525 in the COOH-terminal region of binding with nephrin and was associated with down-modulation of CD2AP, podocin and nephrin glomerular expression. Conclusions. Our findings suggest that CD2AP mutations modify the interaction with CD2 in lymphocytes and alter the composition of the renal slit diaphragm.